2016
DOI: 10.1159/000442180
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renal Progenitors in Renal Regeneration

Abstract: The adult kidney has a remarkable ability to survive injury and restore function despite a limited turnover of cells under physiologic conditions. This accounts both for the tubular and to a lesser extent for the glomerular compartment. It is an ongoing debate whether renal repair is carried out by self-duplication/de-differentiation of mature resident renal cells, or by specialized renal progenitors residing in specific niches or by circulating bone marrow-derived stem cells. In this review, the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Despite the limited turnover rate of renal cells under physiologic conditions, the adult kidney has some ability to cope with injuries and restore its function. 1 Indeed, human kidneys replace approximately one tubular cell per nephron per day while maintaining normal renal function. 2 However, the mechanisms underlying tubular regeneration are still not fully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited turnover rate of renal cells under physiologic conditions, the adult kidney has some ability to cope with injuries and restore its function. 1 Indeed, human kidneys replace approximately one tubular cell per nephron per day while maintaining normal renal function. 2 However, the mechanisms underlying tubular regeneration are still not fully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, previous studies performed by us and other groups strongly suggested that after different modes of kidney injury, regenerating renal cells are not related to BM but originate from resident cells, including vascular, tubular, and interstitial progenitor subpopulations. 2227 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are reports of progressive tubular cell function loss in LS patients [ 57 ]. Although the origin/nature of renewable stem cell-like cells in the post-natal kidney is still controversial [ 64 66 ], there is a body of evidence supporting their existence and relevance for maintaining renal functionality [ 66 68 ]. Our work suggests the availability of such cell replenishing pool may be compromised in LS patients.…”
Section: Discussionmentioning
confidence: 99%